Narrative Empathy, Vulnerability and Ethics of Care in William Trevor’s Fiction (ENTHYMEMA, 2020)
This essay engages with the relationship between ethics and literature. To this end, it addresses the theoretical framework of narrative empathy as illustrative of the supposed ethical power of literary writing. Using a corpus of William Trevor’s fiction, Reading Turgenev (1991) and Love and Summer (2009) as case study, the essay suggests that Trevor’ use of metafictional devices (metalepses and the disnarrated), temporal disarray and multifocal perspectives tends to complicate the general assumption of empathy as necessarily easy and spontaneous. These formal strategies of literary representation manifest the underlying manipulative nature of narrative empathy, confronting readers with the ethical effects of empathy. In so doing, Trevor’s fiction edges towards the aesthetics of vulnerability in that it entails an ethics of reading and writing that reminds the reader of the darkest sides of human existence.